Reduced Verbal Memory Retention is Unrelated to Sleep Disturbance During Pregnancy. (7th June 2012) - Wilson, Danielle L; Barnes, Maree; Ellett, Lenore; Permezel, Michael; Jackson, Martin; Crowe, Simon F
<x xml:space="preserve">Abstract</x> This study investigated episodic and procedural memory retention in early and late pregnancy and whether memory retention was related to sleep disruption. Twenty‐six women in the third trimester of pregnancy, 20 women in the first trimester of pregnancy, and 24 non‐pregnant controls were administered a battery of verbal and visual episodic memory tasks and two procedural memory tasks before undergoing an overnight sleep study. Memory retention was assessed the following morning. Results indicated that as compared with controls, both pregnant groups had reduced retention in verbal episodic memory but were unimpaired on visual and procedural memory tasks. The pregnant women also demonstrated significant disruption of sleep patterns. Reduced verbal memory retention during pregnancy was not attributable to any measure of sleep; however, small correlations between some indices of sleep and memory do not allow full dismissal of the sleep‐dependent memory consolidation hypothesis.